2019
DOI: 10.1016/j.msksp.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of upper limb neurodynamic tests for the assessment of peripheral neuropathic pain: A systematic review

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…One systematic review concluded that, despite the high sensitivity, the clinical neurological examination is associated with misclassification in cervical radiculopathy, due to its poor specificity [12]. These con-tradictory results might be explained by the difference in reference standard used (needle electromyography versus clinical presentation combined with medical imaging) and patient population (patients with Grade III neck pain [28] versus patients suspected for cervical radiculopathy).…”
Section: Clinical Neurological Examinationmentioning
confidence: 99%
“…One systematic review concluded that, despite the high sensitivity, the clinical neurological examination is associated with misclassification in cervical radiculopathy, due to its poor specificity [12]. These con-tradictory results might be explained by the difference in reference standard used (needle electromyography versus clinical presentation combined with medical imaging) and patient population (patients with Grade III neck pain [28] versus patients suspected for cervical radiculopathy).…”
Section: Clinical Neurological Examinationmentioning
confidence: 99%
“…Leprosy patients test positive when submitted to Neurodynamic Assessment of lower limbs [23] . But, even when the tests do not reproduce the symptoms in the affected nerves, characterizing negative tests, studies suggest that a neuropathy cannot be ruled out yet, this can mean a more severe lesion with demyelination of the fibres [33] (as occurred in degree 2 patients that tested negative in the lower limbs in our analysis), producing a possible false negative result [18] , thus explaining the low sensitivity of the NDA in lower limbs, because low sensitivity produces more false negative results [18] .…”
Section: Discussionmentioning
confidence: 99%
“…They should be interpreted in the context of a loss of function tests of small fibres in a domain [32] . Combining anamnesis and clinical history is an important tool to make the differential diagnosis, where the combination of negative neurodynamic test results could be used to rule out a disorder in the peripheral nerves; with limited evidence, they are relevant in cervical radiculopathies [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The upper limb neurodynamic test 1 (ULNT1) consists of a series of movements constructed to stress various parts of the nervous system and is regarded to be capable of detecting increased nerve mechanosensitivity [ 1 , 2 ]. Clinicians use range of motion (ROM) and sensory responses to evaluate neurodynamic tests and compare sides and/or relate results to normal values in order to diagnose upper extremity peripheral neuropathic pain [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%